Evolution as a Religion: A Comparison of Prophecies - Midgley, Mary (Zygon, 1987)
Abstract. The idea of evolution functions today as a myth as well as a scientific theory. This use distorts it in some surprising ways. In particular, predictions of the predestined future development of superhumans (Omega Man) are sometimes treated by scientists as if they were an established part of the theory of evolution. Since they rest on the endless–escalator model of evolution, incompatible with Darwinian methods and not separately argued for, they have no standing at all. This phenomenon, and others like it, seem to indicate spiritual needs which are being ignored and thus finding illicit satisfaction. The position is dangerous and needs more attention.